2021
DOI: 10.3390/biomedicines9080939
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of TEX264-Mediated ER-Phagy Contributes to the Therapeutic Effect of Glycycoumarin against APA Hepatotoxicity in Mice

Abstract: Acetaminophen (APA)-induced hepatotoxicity is coupled with the activation of autophagy. We sought to determine whether selective autophagy of the endoplasmic reticulum (ER), termed ER-phagy, is involved in APA hepatotoxicity and to explore its potential as a therapeutic target for APA-induced liver injury (AILI). APA (300 or 600 mg/kg) was administered to male C57BL/6N mice, with and without rapamycin, glycycoumarin (GCM) and N-acetylcysteine (NAC). The results demonstrated that ER-phagy accompanied with ER st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Yan et al ( 2018 ) found that 1 was able to attenuate acetaminophen-induced mitochondrial oxidative stress and c-jun N -terminal kinase (JNK) pathway activation through sustained activation of autophagy, thereby avoiding liver injury. Endoplasmic reticulum phagocytosis, which accompanies endoplasmic reticulum stress, is activated when APAP is overdosed, and treatment with 1 enhances TEX264-mediated endoplasmic reticulum phagocytosis, thereby inhibiting endoplasmic reticulum stress and promoting liver regeneration, significantly reducing liver injury and, thus, its mortality (Yan et al 2021 ). Glycycoumarin ( 1 ) is a potential replacement for N -acetyl cysteine as a therapeutic agent for patients with advanced acetaminophen-induced acute liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al ( 2018 ) found that 1 was able to attenuate acetaminophen-induced mitochondrial oxidative stress and c-jun N -terminal kinase (JNK) pathway activation through sustained activation of autophagy, thereby avoiding liver injury. Endoplasmic reticulum phagocytosis, which accompanies endoplasmic reticulum stress, is activated when APAP is overdosed, and treatment with 1 enhances TEX264-mediated endoplasmic reticulum phagocytosis, thereby inhibiting endoplasmic reticulum stress and promoting liver regeneration, significantly reducing liver injury and, thus, its mortality (Yan et al 2021 ). Glycycoumarin ( 1 ) is a potential replacement for N -acetyl cysteine as a therapeutic agent for patients with advanced acetaminophen-induced acute liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the changes detected by western blot, the number of mitophagic vacuoles (mitophagosomes and mitolysosomes) and LC3 puncta per hepatocyte increased after CSA treatment, when compared with that of APAP-treated alone, as illustrated by TEM (Figure 6B) and immunohistochemical analysis (Figure 6D). Moreover, the continuous decrease in p62 expression verified the unobstructed autophagic flux (Figure 6C), ruling out the possibility that the increase in PINK1, Parkin and LC3-II was caused by blocked autophagy (Yan et al, 2021). To test the involvement of mitophagy, primary hepatocytes were treated with CQ to block the autophagy before CSA treatment.…”
Section: Csa Enhances Mitochondrial Quality Control After Apap Overdosementioning
confidence: 82%
“…Liver tissues were processed as described previously ( Yan et al, 2021 ). The ultrathin sections (70 nm thick) were double stained with uranyl acetate and lead citrate, and viewed under a transmission electron microscope (HT7700, Tokyo, Japan) at 80.0 kV.…”
Section: Methodsmentioning
confidence: 99%